Impasse; Fearing Duty-Free; Anna Bayle [videorecording] - Lazaro, Cheche (Quezon City Probe Productions, 1994)
Summary: Deals with the issue on Total Log Ban bill; the Duty-Free Philippines competing with other department stores; and the exclusive interview of most successful ramp model, Anna Bayle.
Contents: Impasse (15 min.) -- Fearing Duty-Free (20 min.) -- Anna Bayle (15 min.)
VHS.
Keywords: Bayle, Anna; Duty-Free Philippines; Logging -- Philippines; Models (Persons); Shopping Centers -- Philippines